2020
DOI: 10.24251/hicss.2020.014
|View full text |Cite
|
Sign up to set email alerts
|

A Design Methodology for Learning Analytics Information Systems: Informing Learning Analytics Development with Learning Design

Abstract: The paper motivates, presents and demonstrates a methodology for developing and evaluating learning analytics information systems (LAIS) to support teachers as learning designers. In recent years, there has been increasing emphasis on the benefits of learning analytics to support learning and teaching. Learning analytics can inform and guide teachers in the iterative design process of improving pedagogical practices. This conceptual study proposed a design approach for learning analytics information systems wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…Additional work is needed to apply DLAIS in different contexts to validate its generalizability. Since sustainable efforts are needed to realise the use of LAIS in education [24], future works would continue the efforts to apply DLAIS to design effective LAIS. Furthermore, future research may refine DLAIS framework through the development and implementation of different types of LAIS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional work is needed to apply DLAIS in different contexts to validate its generalizability. Since sustainable efforts are needed to realise the use of LAIS in education [24], future works would continue the efforts to apply DLAIS to design effective LAIS. Furthermore, future research may refine DLAIS framework through the development and implementation of different types of LAIS.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have demonstrated the potential of LA for transforming education, there has been little attention paid to the design and implementation of IS with LA capabilities [26]. As a result, the study attempts to propose essential guidelines and a unified framework in hope of that educational IS researchers can unite the forces with the learning scientists and other research communities to push the LA agenda forward This conceptual study responds to the recent calls to perform theory-based LA research [10,19] and to support the application of learning analytics in higher education [18,24]. The framework proposed in this paper is easy to follow to design a theory-based learning analytics information system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is rooted in the analytics domain with emphasis on data mining technology and processes. More recently, Nguyen et al [17] proposed a methodology for designing and developing learning analytics information systems (LAIS) that integrated knowledge from LA and learning design practices. While this methodology tends to the multidisciplinary nature of LA, the teacher is still regarded as a user that does not influence what and to what end the analysis is conducted.…”
Section: Learning Analytics In An Educational Settingmentioning
confidence: 99%
“…Educational data analytics, however rudimentary, has shown its usefulness and potential in a variety of implications such as predicting at‐risk students (Dietz‐Uhler & Hurn, ), analysing student engagement (Siemens & Long, ) and adaptive learning (Larusson & White, ). Nguyen, Gardner, and Sheridan () have summarised the key applications of learning analytics, including visualisation of learning activities, accessing learning behaviour, prediction of student performance, learning personalisation, evaluation of social learning and improving learning materials and tools (Appendix). Learning analytics can support both students and teachers to promote learning outcomes.…”
Section: Theoretical and Conceptual Foundationsmentioning
confidence: 99%